Major yolk protein from sea cucumber (Stichopus japonicus) attenuates acute colitis via regulation of microbial dysbiosis and inflammatory responses. (January 2022) - Feng, Jianhui; Zhang, Lina; Tang, Xue; Hu, Wei; Zhou, Peng
Graphical abstract: We found that dietary supplementation with MYP could attenuate colitis in DSS-induced colitis mice. MYP could prevent tissue damage, diminish occult diarrhea and bleeding, promote anti-inflammatory cytokines and increase the contents of total SCFAs, especially the contents of acetic acid, butyrate and propionate. Moreover, MYP recovered the intestinal microbiome by reorienting the bacterial shift to a healthy state and hindering harmful taxa Bacteroidaceae and enhancing beneficial flora including Verrucomicrobia and Firmicutes. Highlights: Major yolk protein (MYP) could alleviate colitis in mice. MYP promoted the secretion of anti-inflammatory cytokine but not pro-inflammatory cytokine. MYP accelerated the production of SCFAs in the intestine of acute colitis mice. MYP played an important role in regulating the intestinal microbial structure. Abstract: Inflammatory bowel disease afflicted individuals and most medications have adverse effects. The objection of this study is to investigate whether the major yolk protein (MYP) could aid in the remission of colitis. The function of MYP on acute colitis was assessed through a dextran sulfate sodium -induced colitis mice model. Compared to the model group, the anti-inflammatory cytokines increased significantly in the MYP group, whereas the pro-inflammatory cytokines were not significantly different between the model and treatment group. The results also showed that supplementation of MYP improved the shift in microbial community composition of mice with colitis induced by DSS. In addition, MYP supplementation enriched the contents of fecal short-chain fatty acids. The alleviation of MYP on the colitis was probably related to repair the dysbiosis state of colonic microbiota, which thus induced an increase in short-chain fatty acids level and secrete anti-inflammatory cytokines (IL-4 and IL-10). In sum, oral MYP may be a potential candidate for the attenuating of acute colitis.